T76. RETROSPECTIVE ADHD SYMPTOMS IN EARLY PSYCHOSIS: RELATION TO CURRENT CLINICAL SYMPTOMS AND PSYCHOSOCIAL FUNCTIONING. (18th May 2020) - Ereshefsky, Sabrina; Zarubin, Vanessa; Tryon, Valerie; Lesh, Tyler; Carter, Cameron; Niendam, Tara
Abstract: Background: Individuals with psychosis have a 2–5 times higher prevalence of ADHD than the general population. Individuals with early psychosis (EP) with an ADHD history have poorer premorbid social and role functioning, a more challenging symptom course, and poorer long-term psychosocial outcomes. The high degree of overlap in cognitive profiles for both psychosis and ADHD highlights a need for additional research. This project sought to assess the relation between historical report of childhood ADHD symptoms, current psychosis symptoms, and psychosocial functioning in individuals with EP. It is hypothesized that ADHD symptoms will significantly predict functioning. Methods: Individuals, aged 12–30, who experienced the onset of psychotic symptoms in the past 2 years and presented for care at UC Davis EP clinics, were consented and enrolled. Individuals provided retrospective self-report ratings of childhood (between ages 5–12) symptoms of 'inattention' and 'hyperactivity/impulsivity' on the Barkley ADHD Rating Scale. Raters coded current psychosocial (Global Social/Role Functioning [GSF/GRF]) and clinical functioning ([Brief Psychiatric Rating Scale [BPRS], Scale for Assessment of Positive [SAPS] and Negative [SANS] Symptoms) at presentation. BPRS, SAPS, and SANS ratings were combined into 'reality distortion, ' 'poverty, ' and 'disorganization' domains. Medical chart review will be conducted to identify historical report of ADHD diagnosis. Multiple linear regression was used to examine relative contribution of demographic variables, clinical symptoms, and self-reported childhood ADHD symptoms to current social and role functioning. Results: Ninety-eight participants (20.22 years ± 3.95; 39% female; 37% non-Hispanic White; 27% Hispanic; 2% missing demographics) provided complete data. Childhood inattention, poverty, and disorganized symptoms predicted current GSF (R-squared = .39, F[5, 92] = 11.92, p < .001). When assessing demographic differences on outcomes, GSF was rated significantly higher in non-Hispanic White (M = 7.03, SD = 1.80) compared to other non-White participants (M = 6.28, SD = 1.64; t[94] = -2.08, p = .04). With the inclusion of race as a predictor, only poverty and disorganization predicted GSF (R-squared = .40, F[6, 89] = 10.04, p < .001). Poverty symptoms predicted current GRF, while childhood ADHD and other psychosis symptoms did not predict GRF (R-squared = .31, F[5, 92] = 8.09, p < .001). Age significantly correlated with GRF (r = -.31, p = .002). Poverty remained a significant predictor of GRF after including age (R-squared = .37, F[6, 89] = 8.84, p < .001). Additional cognitive correlates, collateral report of childhood ADHD symptoms, prior diagnoses, date of psychosis illness onset, and medication history will also be examined. Discussion: Social functioning was predicted by childhood self-rated inattention and current negative and disorganized symptoms; however, the relation with childhood inattention did not remain after controlling for race/ethnicity. Additional analyses will be conducted to assess if race is presenting as a proxy for other social determinants, including insurance designation, in this sample. Individuals with ADHD experience more difficulty in social settings compared to typically developing peers, possibly due to increased need to use environmental cues; for individuals who go on to develop psychosis, these childhood events are possibly perceived as more stressful, adding to risk for psychosis. However, it is unclear if self-report childhood inattention – captured here as a putative symptom of ADHD – may be better accounted for by premorbid cognitive impairment associated with risk for psychosis. Additional research is required to establish this connection.